New inhibitor of the TAp73 interaction with MDM2 and mutant p53 with promising antitumor activity against neuroblastoma - Gomes, Sara; Raimundo, Liliana; Soares, Joana; Loureiro, Joana B; Leão, Mariana; Ramos, Helena; Monteiro, Madalena N; Lemos, Agostinho; Moreira, Joana; Pinto, Madalena; Chlapek, Petr; Veselska, Renata; et al. (Cancer letters, 2019)
TAp73 is a key tumor suppressor protein, regulating the transcription of unique and shared p53 target genes with crucial roles in tumorigenesis and therapeutic response. As such, in tumors with impaired p53 signaling, like neuroblastoma, TAp73 activation represents an encouraging strategy, alternative to p53 activation, to suppress tumor growth and chemoresistance. In this work, we report a new TAp73-activating agent, the 1-carbaldehyde-3,4-dimethoxyxanthone (LEM2), with potent antitumor activity. Notably, LEM2 was able to release TAp73 from its interaction with both MDM2 and mutant p53, enhancing TAp73 transcriptional activity, cell cycle arrest, and apoptosis in p53-null and mutant p53-expressing tumor cells. Importantly, LEM2 displayed potent antitumor activity against patient-derived neuroblastoma cells, consistent with an activation of the TAp73 pathway. Additionally, potent synergistic effects were obtained for the combination of LEM2 with doxorubicin and cisplatin in patient-derived neuroblastoma cells. Collectively, besides its relevant contribution to the advance of TAp73 pharmacology, LEM2 may pave the way to improved therapeutic alternatives against neuroblastoma.
Keywords: signální transdukce; Signal Transduction; xantony; Xanthones; Apoptosis; HCT116 buňky; regulace genové exprese u nádorů; Humans; neuroblastom; Anticancer therapy; cisplatina; Cisplatin; buňky HT-29; Cell Cycle Checkpoints; nádorový supresorový protein p53; doxorubicin; mutace; Drug Synergism; Antineoplastic Agents; protokoly protinádorové kombinované chemoterapie; Proto-Oncogene Proteins c-mdm2; Doxorubicin; HT29 Cells; Tumor Protein p73; lidé; synergismus léků; apoptóza; protoonkogenní proteiny c-mdm2; p73; Carbaldehydic xanthone; Antineoplastic Combined Chemotherapy Protocols; protinádorové látky; HCT116 Cells; Neuroblastoma; protein p73; Mutation; Gene Expression Regulation, Neoplastic; kontrolní body buněčného cyklu; Tumor Suppressor Protein p53